Influência das condições de processo na granulação de super simples em tambor rotativo - Rodrigues, Rafaella da Fonseca (2012)
Granulation or enlargement of particle size plays an important role in industry for many reasons, such as improving the flowability of powders, reduction of environmental impact and ease to handle. In the fertilizer industry, the granulation can promote slower and more efficient absorption of the nutrients by the plants. The demand for agricultural production is increasing quickly because of the world´s population is growing fast and the Planet has a scarce agriculture resources. Only 24% of the world lands are farmable, 27% can be used just for pastures and 47% of superficies are considered unproductive. Besides of that, to respond of those demands for food will, the world needs to develop new ways to produce more in less land. So, fertilizers have a fundamental importance to the world in order to feed all these people. Fertilizers are mineral actives non renewable and their production must be based on sustainability, this way an granulation production with low costs, high quality and maximum efficiency could increase service life of the reserves. Considering the main importance of Fertilizer in the world´s food production and the criticism of this subject by new generations, the main purpose of this work was found the best conditions in granulation process to reach best granulation efficiency and hardness of particles. Granulation efficiency is an important response of the process since it determines production plant productivity, throughput, and, consequently, the size of industrial equipment, as well as the process and product quality conditions. Both of these characteristics are critical in costs and quality of fertilizers. The granulation´s experiments were performed using ordinary super phosphate from igneous Araxá rock and the evaluated variables were rotation speed, liquid phase, granulation time, fill level of the drum granulator, recycle rate, single super phosphate acidity and dosage of neutralizing. Central Composite Design (CCD) was used to choose the experimental conditions. The correlation between data and process variables was established using Multiple Regression. Images analyses made from microscopic and SEM (scanning electron microscope) with EDX, energy dispersive x-ray detector were used to explain the behavior of process granulation, the mechanism of granule´s formation and quality of granules. The results showed that the best efficiency and the best mechanical proprieties were found in different process conditions. The responses, efficiency of granulation and hardness of the product were found to be greatly dependent on the variable studies. Recycle rate about 1:1, drum´s rotation of 38% cs (critical speed), granulation time around 4-5 min, filling of drum about 11%, super phosphate acidy about 9 10% and small liquid phases showed to be a good condition of work.